IDA18 Retrospective : Investing in Growth, Resilience, and Opportunity through Innovation - International Development Association (World Bank, Washington, DC, 2021)
The landmark 18th Replenishment of the International Development Association (IDA18) featured significant innovation, substantial delivery, and flexibility to respond to urgent country needs, including COVID-19. Paradigm shifts in IDA18 signaled a significant change for IDA. Dedicated Windows address targeted development needs to complement country allocations.